Whitney theorem for copositive approximation in - S. Bhaya, Eman; Z.Abd AL-Sada, Nada (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this research, we have important results about finding the relationship between the best approximation degree and the so called modulus ( or Sendov- Popov modulus ) of order in the space , and the polynomial is copositive with the function at the points in an interval , and also found assessment between the best approximation degree by algebraic polynomial of degree , and the modulus of smoothness of degree , to the function , .